2013
DOI: 10.2478/amcs-2013-0051
|View full text |Cite
|
Sign up to set email alerts
|

A modified convolution and product theorem for the linear canonical transform derived by representation transformation in quantum mechanics

Abstract: The Linear Canonical Transform (LCT) is a four parameter class of integral transform which plays an important role in many fields of signal processing. Well-known transforms such as the Fourier Transform (FT), the FRactional Fourier Transform (FRFT), and the FreSnel Transform (FST) can be seen as special cases of the linear canonical transform. Many properties of the LCT are currently known but the extension of FRFTs and FTs still needs more attention. This paper presents a modified convolution and product the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…In the derived operation, it is found that the result does not meet the requirement of symmetric definition of FT. Further, the derived convolution/correlation operation contains two and ten chirp multiplications on the LHS and RHS, respectively. In 2013, Goel and Singh [29] derived the convolution theorem with different approach. The convolution operation defined in time domain is dependent on time variable only.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…In the derived operation, it is found that the result does not meet the requirement of symmetric definition of FT. Further, the derived convolution/correlation operation contains two and ten chirp multiplications on the LHS and RHS, respectively. In 2013, Goel and Singh [29] derived the convolution theorem with different approach. The convolution operation defined in time domain is dependent on time variable only.…”
Section: Research Articlementioning
confidence: 99%
“…The origin of LCT is in quantum mechanics and a brief overview may be found in [14]. As a generalisation of the FT, FRFT and FST, the basic theories of the LCT have been developed including sampling the signals [15][16][17][18][19][20][21][22][23][24], convolution and correlation operations, discrete approximations to the transforms [25][26][27][28][29][30][31][32][33][34][35][36][37][38]a n ds oo n ,w h i c h augment the theoretical system of the LCT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be regarded as a generalization of many mathematical transforms such as the Fourier transform, Laplace transform, the fractional Fourier transform, and the Fresnel transform. Many fundamental properties of this extended transform are already known, including shift, modulation, convolution, and correlation and uncertainty principle, for example, in [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The quaternion algebra over R, denoted by H, is an associative noncommutative four-dimensional algebra: (1) which obeys the following multiplication rules: ij = −ji = k, jk = −kj = i, ki = −ik = j, i 2 = j 2 = k 2 = ijk = −1.…”
Section: Introductionmentioning
confidence: 99%